2018
DOI: 10.1111/fcp.12415
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of dexamethasone on development of the fetal rat ovary

Abstract: Dexamethasone (Dx) is often used in obstetric practice to promote fetal lung maturation and to prevent respiratory distress syndrome when the risk of preterm delivery persists. This therapy enables survival of the newborn, but also is associated with deleterious effects on the offspring, such as reproductive disorders. The aim of this study was to determine specifically whether prenatal exposure to Dx disturbs the physiological balance between proliferation and apoptosis of germinative cells (GC) in the ovary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Intrauterine organ development is vulnerable to adverse environments such as prenatal drug use, and many different kinds of drugs have been shown to damage the development of the same organ ( Table 1 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ). The liver is the crucial organ for the metabolism of many exogenous compounds, including drugs.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrauterine organ development is vulnerable to adverse environments such as prenatal drug use, and many different kinds of drugs have been shown to damage the development of the same organ ( Table 1 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ). The liver is the crucial organ for the metabolism of many exogenous compounds, including drugs.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…Hippocampal, bone, and gonadal development are also vulnerable to a variety of drugs. Anesthetics 28 , 29 , 30 , 31 , 32 , antipsychotics 33 , 34 , 35 , 36 , and synthetic glucocorticoids 37 have been shown to affect hippocampal development; synthetic glucocorticoids 38 , 39 , antibiotics 12 , 40 , anticancer drugs 41 , 42 , antimalarials 43 , antiviral drugs 44 , NSAIDs 45 , and synthetic estrogen 46 have been shown to affect bone development and chondrogenesis; NSAIDs 47 , 48 , 49 , antipyretic-analgesic drugs 50 , 51 , synthetic glucocorticoids 52 , 53 , synthetic estrogens 54 , 55 , and hypoglycemic agents 56 can affect testicular or ovarian development. It is not difficult to find that studies on drug-induced organ developmental toxicity are mainly based on animal models.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the uterus, it was described that an increase of GCs causes a reduction of embryos implantation rate [58]. Ovaries exposed to GCs treatment undergo several damages such as steroidogenesis alteration, histological impairment [59], and reduction of the total number of germ cells and ovarian volume [60]. In oocytes, GCs impair their reproductive competence, inducing oocytes apoptosis [61].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…One study showed that maternal stress in guinea pigs increased T levels in female offspring during adulthood [ 212 ], whereas prenatal DEX led to reduced circulating follicle-stimulating hormone and luteinizing hormone in peripubertal rats [ 213 ] and lower serum E2 in adult female offspring [ 214 ]. The most consistent results reported in female offspring were alterations in the onset of puberty and variations in the length of estrus stages [ 215-220 ] as well as decreased numbers of healthy primordial follicles [ 221 , 222 ], likely due to the proapoptotic action of DEX reported on human and rat fetal ovaries [ 223 , 224 ]. Thus, developmental GC overexposure has the ability to disrupt later-life processes in female offspring that depend on sex-steroid action.…”
Section: Evidence For Developmental Sex-steroid Disruption By Abermentioning
confidence: 73%